Uma sequência didática para o ensino de parábola enquanto lugar geométrico - Lopes, Sandra Pereira (2014)
The goal of this study is to investigate the comprehension of the definitions of parabola as locus by second year high school students based on an instructional sequence in which the research subjects would produce treatments and conversions of Registers of Semiotic Representations, concerning the mathematical object parabola. In this sense, we seek to answer the following research question: Does a teaching sequence which articulates the conversion of registers, from the notion of locus results in ownership by the student's knowledge of the parabola? We applied the teaching sequence to five high school students and, as a theoretical foundation for the research, we adopted the Registers of Semiotic Representation of Raymond Duval and the Theory of Didactic Situations of Guy Brousseau. The approach of this research was qualitative and, as a methodology, we followed the assumptions of Engineering Curriculum. Observing the productions of the subjects in the course of the activities of the sequence, we found that they have appropriated the definition of parabola from the notion of locus in the domain of plane and analytic geometries, they performed the conversions and treatments in the registers and, at the end of the study, they could recognize that the mathematical object parabola is not only the graphic representation of a quadratic function